Nautical chart for water polo - International trend and athlete development program in Japan - Enomoto, I. (Japanese Journal of Sciences in Swimming and Water Exercise, 2005)
International Olympic Committee had evaluated after 2004 Athens Olympic Games that history and tradition of Water Polo were superior to other Olympic sports. They had also evaluated that universality and TV coverage of Water Polo were inferior to other sports. International Swimming Federation has recognized the urgent need to change. They had makes some revolution such as enlargement of international tournament for five continents and progress in the referring. Additionally they had decided some changes in international rules to increase goals and spectacle scenes. These innovative changes will give some advantages for small players like Japanese than before. Some Japanese National Sports Federations has been pointed out that old athlete development system in Japan will not be stand against international competition scene. Most of false for these systems is excessive dependence on public education system. They lack coherent training methods and close relationship between programs of each coaches. A new long-term athlete development program must be established soon. Can Japan Water Polo ride on the strength of new Water Polo rules by carrying a new development program?